The Effect of Stocking Density on Performance of Padjadjaran Broiler Quail - Rina Marwati; Iwan Setiawan; Endang Sujana (Fakultas Peternakan, Universitas Padjadjaran, 2023)
This research's purpose was to determine the effect of stocking density on the performance of Padjadjaran broiler quails (feed consumption, body weight gain, and feed conversion ratio). This experiment used 90 day old quails (DOQ) of Padjadjaran broilers quail and raised them for 6 weeks from 23 January until 5 March 2023 at the Quail Breeding Center, Faculty of Animal Husbandry, Padjadjaran University. The research used an experimental method with a complete randomized design (CRD). The stocking density treatment was applied to quails starting at the age of 3 to 6 weeks, consisting of P1 (stocking density of 40 birds per m2), P2 (stocking density of 50 birds per m2), and P3 (stocking density of 60 birds per m2). Each treatment was replicated 6 times with each replicate containing 5 quails. Data on feed consumption, body weight gain and feed convertion ratio were analyzed by variance analysis and to determine differences between treatments were tested using Duncan's Multiple Range Test. The results showed that stocking density had no effect (P>0.05) on the performance of Padjadjaran broiler quails. Based on the results of the study, we concluded that stocking densities of up to 60 birds per m2 still provide a good performance in Padjadjaran broiler quails.